Isolation controls reestablishment mechanisms and post‐drying community structure in an intermittent stream. Issue 2 (3rd January 2023) - Fournier, Robert J.; de Mendoza, Guillermo; Sarremejane, Romain; Ruhi, Albert
Abstract: Biota in disturbance‐prone landscapes have evolved a variety of strategies to persist long term, either locally ( resistance ) or by regional recolonization ( resilience ). Habitat fragmentation and isolation can limit the availability of recolonization pathways, and thus the dynamics of post‐disturbance community reestablishment. However, empirical studies on how isolation may control the mechanisms that enable community recovery remain scarce. Here, we studied a pristine intermittent stream (Chalone Creek, Pinnacles National Park, California) to understand how isolation (distance from a perennial pool) alters invertebrate community recolonization after drying. We monitored benthic invertebrate reestablishment during the rewetting phase along a 2‐km gradient of isolation, using mesh traps that selected for specific recolonization pathways (i.e., drift, flying, swimming/crawling, and vertical migration from the hyporheic). We collected daily emigration samples, surveyed the reestablished benthic community after 6 weeks, and compared assemblages across trap types and sites. We found that isolation mediated migration dynamics by delaying peak vertical migration from the hyporheic by ca. 1 day on average per 250 m of dry streambed. The relative importance of reestablishment mechanisms varied longitudinally–with more resistance strategists (up to 99.3% of encountered individuals) in the upstream reaches, and increased drift and aerial dispersers in the more fragmented habitats (up to 17.2% and 18%, respectively). Resistance strategists persisting in the hyporheic dominated overall (88.2% of individuals, ranging 52.9%–99.3% across sites), but notably most of these organisms subsequently outmigrated downstream (85.6% on average, ranging 52.1%–96% across sites). Thus, contrary to conventional wisdom, resistance strategists largely contributed to downstream resilience as well as to local community recovery. Finally, increased isolation was associated with a general decrease in benthic invertebrate diversity, and up to a 3‐fold increase in the relative abundance of drought‐resistant stoneflies. Our results advance the notion that understanding spatial context is key to predicting post‐disturbance community dynamics. Considering the interaction between disturbance and fragmentation may help inform conservation in ecosystems that are subject to novel environmental regimes.